2017
DOI: 10.1007/s10856-017-5931-6
|View full text |Cite
|
Sign up to set email alerts
|

Anti-fibronectin aptamers improve the colonization of chitosan films modified with D-(+) Raffinose by murine osteoblastic cells

Abstract: The aim of the present study was to investigate how the enrichment of chitosan films with anti-fibronectin aptamers could enhance scaffold colonization by osteoblasts, by improving their adhesion and accelerating their proliferation. Chitosan discs were enriched with excess of anti-fibronectin aptamer. Aptamer adsorption on chitosan was monitored by measuring aptamer concentration in the supernatant by spectrophotometry, as well as its release, while functionalization was confirmed by labelling aptamers with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
40
0
6

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(48 citation statements)
references
References 28 publications
2
40
0
6
Order By: Relevance
“…As in the field of biomaterials, the ESI‐MS and MS/MS data obtained in our study presented, as key feature, the ability of a simple HDX approach to provide useful and direct insights into the structural dynamics of a FN fragment involved in chitosan surface functionalization in the presence or absence of a selective aptamer. As previously reported aptamers did not affect the amount of adsorbed FN, but presumably influenced its conformation enhancing its biological activity toward osteoblasts adhesion and growth. Here, FN peptides involved in interactions with aptamers were identified and the MS data indicated the improved functionality of FN on chitosan when aptamers were used as selective spacer.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…As in the field of biomaterials, the ESI‐MS and MS/MS data obtained in our study presented, as key feature, the ability of a simple HDX approach to provide useful and direct insights into the structural dynamics of a FN fragment involved in chitosan surface functionalization in the presence or absence of a selective aptamer. As previously reported aptamers did not affect the amount of adsorbed FN, but presumably influenced its conformation enhancing its biological activity toward osteoblasts adhesion and growth. Here, FN peptides involved in interactions with aptamers were identified and the MS data indicated the improved functionality of FN on chitosan when aptamers were used as selective spacer.…”
Section: Discussionsupporting
confidence: 57%
“…In order to improve the ability of chitosan to act as a substrate for cell growth, the preparation of chitosan films in the presence of phosphates and D‐(+)‐raffinose was described, which positively contributed to the growth of WI‐38 and HUVEC cells on this biomaterial. The same model however was not very efficient in supporting the growth of osteoblastic cells, so further functionalization of these hydrogels was performed to improve their biocompatibility by exploiting the binding affinity of chitosan for sulfur‐containing components, such as thiol‐modified gelatin, or by means of aptamers …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is then clear that innovation in the field of loco-regional drug administration is a viable strategy to increase the effectiveness of chemotherapy and to reduce toxic side effects for lung cancer patients undergoing chemotherapy (38). In the case of the two materials studied in this research, chitosan, despite being a material used often for implants and for tissue engineering (39) and considered biocompatible and relatively non pro-inflammatory (40), showed a strong foreign body reaction and released cisplatin at an extremely low rate in vitro as well as in vivo. However, recently it has been reported that chitosan can show mild to moderate chronic inflammation (41) and foreign body reaction (42) in the case of crosslinked chitosan derivatives.…”
Section: Discussionmentioning
confidence: 98%
“…To bypass these issues, aptamers were then proposed. One such approach was reported by Galli, et al [18] and Parisi, et al [19]. In these papers, anti-Fibronectin aptamers were used as docking points on hyaluronic acid-polyethylenglycole hydrogels and chitosan hydrogels respectively.…”
mentioning
confidence: 99%